A Comparative Study on the Eye Colour Variations in Racing Pigeons (Columba livia domestica) - Esakkiammal M,; Dr. Sheeba Rajakumari D V,; Jenci Dilda I,; , Mahaboobjan S, (The Bioscan, 2024)
In the animal kingdom, there is an extensive variation in colouration and pigmentation of iris of the eyes across the species. Racing pigeons (Columba livia domestica) have three common iris colours. They are yellow - orange, pearl (white), and bull (dark brown), segregating in a single species, thereby providing a unique opportunity to identify the genetic basis of the iris coloration. A total of sixty pigeons were collected from three different locations for the study. Pigeons with a yelloworange eye colour are the most numerous among a total of 60 racing pigeons. The total number of pigeons was divided into different eye colours based on pigmentation and structural colouration.